A carboxyl-terminal interaction of lamin B1 is dependent on the CAAX endoprotease Rce1 and carboxymethylation. - Maske, C; Hollinshead, MS; Higbee, N; Bergo, M; Young, S; Vaux, D (2003)
The mammalian nuclear lamina protein lamin B1 is posttranslationally modified by farnesylation, endoproteolysis, and carboxymethylation at a carboxyl-terminal CAAX motif. In this work, we demonstrate that the CAAX endoprotease Rce1 is required for lamin B1 endoproteolysis, demonstrate an independent pool of proteolyzed but nonmethylated lamin B1, as well as fully processed lamin B1, in interphase nuclei, and show a role for methylation in the organization of lamin B1 into domains of the nuclear lamina. Deficiency in the endoproteolysis or methylation of lamin B1 results in loss of integrity and deformity of the nuclear lamina. These data show that the organization of the nuclear envelope and lamina is dependent on a mechanism involving the methylation of lamin B1, and they identify a potential mechanism of laminopathy involving a B-type lamin.